Climatic heterogeneity and vegetation diversity in southern Ecuador investigated by phytoindication - Richter, Michael (2005)
In this paper hygric estimations by similarity analysis based on epiphytism are combined with singular measurements of temperatures 60 cm below ground to generate an accurate cartography of hygro-thermal patterns within a complex relief in southern Ecuador. The method improves comprehension of regional circulation patterns as well as providing an idea of the potential vegetation distribution. This can be of further help to comprehend the various environmental factors that support one of the highest levels of floral diversity in the Neotropics and even on the global scale. The method described is also applicable for the Andean part of northern Peru with its similarly complex orography.